2022
DOI: 10.3389/fcell.2022.789841
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelasticity, Like Forces, Plays a Role in Mechanotransduction

Abstract: Viscoelasticity and its alteration in time and space has turned out to act as a key element in fundamental biological processes in living systems, such as morphogenesis and motility. Based on experimental and theoretical findings it can be proposed that viscoelasticity of cells, spheroids and tissues seems to be a collective characteristic that demands macromolecular, intracellular component and intercellular interactions. A major challenge is to couple the alterations in the macroscopic structural or material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 692 publications
(974 reference statements)
0
13
0
Order By: Relevance
“…Although there are numerous studies involving decellularized tissue ECM, only a small portion of these demonstrated the effect of decellularization on the biophysical properties of hydrogels, such as mechanical stability and stiffness. It has been established in the literature that mechanical characteristics have an important impact on cell growth, motility, and tissue homeostasis . In Kingshott et al’s work, it was postulated that matrix stiffness has a direct effect on cell behavior as cells continuously remodel the matrix .…”
Section: Discussionmentioning
confidence: 99%
“…Although there are numerous studies involving decellularized tissue ECM, only a small portion of these demonstrated the effect of decellularization on the biophysical properties of hydrogels, such as mechanical stability and stiffness. It has been established in the literature that mechanical characteristics have an important impact on cell growth, motility, and tissue homeostasis . In Kingshott et al’s work, it was postulated that matrix stiffness has a direct effect on cell behavior as cells continuously remodel the matrix .…”
Section: Discussionmentioning
confidence: 99%
“…Natural tissue ECMs and most biological materials display complex mechanical properties, exhibiting time-dependent properties including viscoelasticity, viscoplasticity, non-linear elasticity and heterogenous behaviour depending on their location within the body [ 58 , 59 ]. The ECM can affect cell migration both regarding time and force scales of cell-ECM interactions where cells perceive the environment through their membrane and respond by reorganizing cytoskeletal elements.…”
Section: Implications Of Hydrogel Properties On Migrating Cellsmentioning
confidence: 99%
“…47 Unlike elastic hydrogel substrates, viscoelastic hydrogels, based on reversible ionic or dynamic covalent bonds, result in stress relaxation and energy dissipation, leading to time-dependent cytoskeletal rearrangement and cell traction forces. 48,49 For instance, relaxed stress in 3D dynamic hydrogel networks facilitated integrin clustering and focal adhesion complex formation, followed by transferring mechanical signals to the actin component of the cytoskeleton. 50 This, in turn, enhanced cell contractility and hydrogel network deformations, as evidenced by the increased expression of phosphorylated myosin light chain and strong traction force as compared to those in nondynamic hydrogels.…”
Section: Viscoelasticitymentioning
confidence: 99%